The Exceptionally Large Chloroplast Genome of the Green Alga Floydiella terrestris Illuminates the Evolutionary History of the Chlorophyceae - Brouard, Jean-Simon (Oxford University Press, 2010)
The Chlorophyceae, an advanced class of chlorophyte green algae, comprises five lineages that form two major clades (Chlamydomonadales + Sphaeropleales and Oedogoniales + Chaetopeltidales + Chaetophorales). The four complete chloroplast DNA (cpDNA) sequences currently available for chlorophyceans uncovered an extraordinarily fluid genome architecture as well as many structural features distinguishing this group from other green algae. We report here the 521,168-bp cpDNA sequence from a member of the Chaetopeltidales (Floydiella terrestris), the sole chlorophycean lineage not previously sampled for chloroplast genome analysis. This genome, which contains 97 conserved genes and 26 introns (19 group I and 7 group II introns), is the largest chloroplast genome ever sequenced. Intergenic regions account for 77.8% of the genome size and are populated by short repeats. Numerous genomic features are shared with the cpDNA of the chaetophoralean Stigeoclonium helveticum, notably the absence of a large inverted repeat and the presence of unique gene clusters and trans-spliced group II introns. Although only one of the Floydiella group I introns encodes a homing endonuclease gene, our finding of five free-standing reading frames having similarity with such genes suggests that chloroplast group I introns endowed with mobility were once more abundant in the Floydiella lineage. Parsimony analysis of structural genomic features and phylogenetic analysis of chloroplast sequence data unambiguously resolved the Oedogoniales as sister to the Chaetopeltidales and Chaetophorales. An evolutionary scenario of the molecular events that shaped the chloroplast genome in the Chlorophyceae is presented.